The International Conference on Climate Services 6: Advancing the knowledge and practice of climate services for climate resilience - Jordan, Pamela (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
On February 11-13, 2020, over 200 attendees gathered from all over the world for the Sixth International Conference on Climate Services held in Pune, India. The event, which took place at the Indian Institute of Tropical Meteorology (IITM), was supported by India's Ministry of Earth Sciences, the UK Foreign Commonwealth and Development Office (FCDO), and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). Participants represented a diverse group of institutions from NGOs, international organizations, research institutions, and government agencies. Participants gathered to hear presentations on "advancing the knowledge and practice of climate services for climate resilience,” across a set of thematic topics on the state of the practice of climate services, the state of knowledge, and building resilience. ICCS is the premiere climate services event, organized jointly by the Global Framework for Climate Services, an international effort coordinated by the World Meteorological Organization, and the Climate Services Partnership (CSP), an informal platform for knowledge sharing and collaboration. Climate services, which provide timely, tailored information and knowledge to decision-makers – generally in the form of tools, products, websites, or bulletins – are an important part of improving our capacity to manage climate-related risks.